Graph-based pose estimation of texture-less surgical tools for autonomous robot control - Xu,H; Runciman,M; Cartucho,J; Xu,C; Giannarou,S (IEEE, 2023)
In Robot-assisted Minimally Invasive Surgery (RMIS), the estimation of the pose of surgical tools is crucial for applications such as surgical navigation, visual servoing, autonomous robotic task execution and augmented reality. A plethora of hardware-based and vision-based methods have been proposed in the literature. However, direct application of these methods to RMIS has significant limitations due to partial tool visibility, occlusions and changes in the surgical scene. In this work, a novel keypoint-graph-based network is proposed to estimate the pose of texture-less cylindrical surgical tools of small diameter. To deal with the challenges in RMIS, keypoint object representation is used and for the first time, temporal information is combined with spatial information in keypoint graph representation, for keypoint refinement. Finally, stable and accurate tool pose is computed using a PnP solver. Our performance evaluation study has shown that the proposed method is able to accurately predict the pose of a textureless robotic shaft with an ADD-S score of over 98%. The method outperforms state-of-the-art pose estimation models under challenging conditions such as object occlusion and changes in the lighting of the scene.